Coronavirus Disease (COVID-19) Testing in Asymptomatic Patients Planned for Day Care Systemic Therapy: A Tertiary Cancer Center Experience - Ovett, Jerin; Dhanushkodi, Manikandan; Radhakrishnan, Venkatraman; Mehra, Nikita; Kalaiarasi, Jayachandran Perumal; Selvarajan, Gangothri; Rajan, Arun Kumar; Karunakaran, Parathan; Kesana, Sivasree; Sagar, Tenali Gnana (Indian Journal of Medical and Paediatric Oncology, 2021)
Introduction The Indian Council of Medical Research recommends coronavirus disease 2019 (COVID-19) testing for asymptomatic patients only in hospitalized condition or those seeking hospitalization for chemotherapy.Materials and Methods This was a retrospective study to assess the incidence of asymptomatic COVID-19 positivity among asymptomatic, adult patients who were planned for systemic therapy as day care at a tertiary care cancer center. COVID-19 testing was done by reverse transcriptase-polymerase chain reaction by throat/nasopharyngeal swab once before the first cycle of systemic therapy and once every 3 weeks until completion of systemic therapy.Results A total of 824 systemic therapies were delivered in day care from May 7 to June 20, 2020. Among the 761 COVID-19 testing done before systemic therapy, 11 patients were COVID-19 positive (1.45%, 95% confidence interval: 0.60–2.29). Among the 11 patients, 45% were negative before the first systemic therapy but tested positive before subsequent cycles. Among the asymptomatic COVID-19-positive patients, 54% were hospitalized for observation and 46% were on home quarantine for 14 days. None of them received investigational therapy or traditional treatment for COVID-19. None of the patients needed admission in the intensive care unit or oxygen/ventilatory support. There was no mortality among these patients. All patients turned COVID-19 negative at a median of 9 days. Currently, 45% (n = 5/11) of the patients have resumed systemic therapy.Conclusion The incidence of asymptomatic COVID-19 positivity among adult cancer patients planned for day care systemic therapy is low (1.45%). Hence, COVID-19 testing should be done after informed/shared decision with the patient/attendants. Repeat COVID-19 testing before each cycle of systemic therapy is preferable, as 45% of the patients were COVID-19 negative before the first cycle of systemic therapy and turned positive before subsequent cycles in the present study. There was no morbidity or mortality in this cohort of asymptomatic COVID-19-positive cancer patients.
Keywords: COVID-19 infection; COVID-19 testing; day care systemic therapy; reverse transcriptase-polymerase chain reaction